2023
DOI: 10.1021/acs.jnatprod.3c00562
|View full text |Cite
|
Sign up to set email alerts
|

Natural Enfumafungin Analogues from Hormonema carpetanum and Their Antifungal Activities

Zhi Cheng,
Wei Wu,
Yu Liu
et al.

Abstract: Ibrexafungerp, an inhibitor of fungal β-(1,3)-Dglucan synthase, represents the first new class of antifungals to be approved in the last 20 years. Ibrexafungerp is a semisynthetic derivative of the naturally occurring triterpene glycoside enfumafungin. In order to search for new analogues of enfumafungin and to probe its biosynthesis, we undertook a reinvestigation of Hormonema carpetanum, which led to the isolation of two new analogues, enfumafungins B and C, together with enfumafungin. Due to the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…niger R330 (Table S4). Further analysis of the structure–activity relationship revealed that the cleaved E-ring was essential for the antifungal activity, as observed in the comparison between compounds 1 and 12 , as well as between compounds 8 and 4 , which aligns with previous findings . Moreover, compound 8 demonstrated higher potency than compound 11 , suggesting that C3β- d -glucopyranose plays a critical role in its activity.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…niger R330 (Table S4). Further analysis of the structure–activity relationship revealed that the cleaved E-ring was essential for the antifungal activity, as observed in the comparison between compounds 1 and 12 , as well as between compounds 8 and 4 , which aligns with previous findings . Moreover, compound 8 demonstrated higher potency than compound 11 , suggesting that C3β- d -glucopyranose plays a critical role in its activity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Further analysis of the structure−activity relationship revealed that the cleaved E-ring was essential for the antifungal activity, as observed in the comparison between compounds 1 and 12, as well as between compounds 8 and 4, which aligns with previous findings. 46 Moreover, compound 8 demonstrated higher potency than compound 11, suggesting that C3β-D-glucopyranose plays a critical role in its activity. Therefore, both the E-ring cleavage enzyme FsoE and chimeric enzyme FsoA hold the potential for the transformation of biologically active enfumafungin-type antibiotics.…”
Section: Structure−activity Analysis Of Enfumafungin-typementioning
confidence: 99%
“…Enfumafungin analogues were isolated; they are enfumafungin B and C. Both compounds were effective against clinically relevant C. auris with the MIC of 64 µg/mL. Further molecular docking studies confirmed that these compounds binded in transmembrane region of FKS1 of β-(1,3)-D-glucansynthase [63].…”
Section: Natural Products Against Candida Aurismentioning
confidence: 93%
“…Both compounds were effective against clinically relevant C. auris with a MIC of 64 µg/mL. Further molecular docking studies confirmed that these compounds bonded in the transmembrane region of FKS1 of β-(1,3)-D-glucansynthase [ 64 ].…”
Section: Therapeutic Optionsmentioning
confidence: 99%